Business Consulting Support to Small and Medium Enterprises in Lithuania - Urbonavičius, Sigitas; Dikčius, Vytautas (Ekonomika, 2005)
The sector of small and medium enterprises (SMEs) is important to the Lithuanian economy and its social development. However, small and medium enterprises are rather vulnerable due to their limited resources and other specific characteristics. Therefore they often are supported by governmental and international organisations. Many support programs concentrate on providing additional financing; others concentrate on the educational aspect, which includes training and business advice. Encouragement to use professional business consulting services belongs to the latter group and is rather unique. This impacts the overall outsourcing, transparency of operation and partnership in general. This educational aspect is specifically important to SMEs in transition economies, where traditions of using services of business consultants are very short.The article analyses how SMEs selected various types of business advice during a relatively long period of Lithuanian economy transformation. Choice differences between decisions of small (up to 50 employees) and medium (50-249 employees) companies are observed and analysed. The article analyses also the effects of consulting services on SMEs growth in terms of their sales and number of employees. This analysis allows indicating types of business consulting services that influenced the growth of enterprises more than others.The research is based on a survey that included over 300 Lithuanian small and medium enterprises.